Rheological properties of ice cream emulsion prepared from lipase-catalyzed transesterified palm kernel olein:anhydrous milk fat mixture - Liew, M.Y.B.; Ghazali, H.M.; Yazid, A.M.; Lai, O.M.; Chow, M.C.; Yusoff, M.S.A.; Long, K. (Wiley, 2001)
The effect of different fat sources used in the preparation of ice cream emulsions was investigated. Anhydrous milk fat (AMF), a mixture of unmodified palm kernel olein (PKO) and AMF (70:30, w/w) and enzyme-transesterified PKO:AMF (70:30, w/w) mixture were used in the preparation of the emulsions. Transesterification was catalyzed by mycelium-bound lipase from Rhizomucor miehei. Rheological and viscoelastic properties measured were the creep compliance, controlled-stress steady state flow and frequency sweep profiles. Results indicate that emulsion prepared using transesterified PKO:AMF (TE-PKO:AMF) exhibited a different rheological behavior from that of AMF alone, and the unmodified PKO:AMF (70:30) blend. Frequency sweep profiles showed that the G = values of both AMF and TE-PKO:AMF emulsions were higher than their G at values, indicating that these emulsions were dominated by the elastic component over all frequencies measured. On the other hand, the PKO:AMF emulsion was dominated by viscous components at low frequency. A plot of viscosity versus log shear rate illustrated that the ice cream emulsion made from TE-PKO:AMF was more viscous than those of unmodified PKO:AMF and AMF. The lower creep compliance showed a stronger emulsion in the TE-PKO:AMF than that of the unmodified PKO:AMF. Since high viscosity and greater strength are some of the desired properties in ice cream emulsion, this suggests that transesterification of PKO:AMF (70:30, w/w) can be used to produce a fat that is suitable for use in the preparation of ice cream emulsions.